Project management methods and tools as a means of improving the efficiency of health facilities in modern conditions - Chukhno, Inna; Kuznetsova, O. (My University, 2018)
The article considers the necessity of finding new approaches to the management of health care institutions in the current conditions of the reform in health industry. It is proposed to use the project approach and separate elements, methods and technologies of project management in this area.
Keywords: project management; project management tools; management of health care institutions